2020
DOI: 10.1186/s12884-020-03267-2
|View full text |Cite
|
Sign up to set email alerts
|

Rate, determinants, and causes of stillbirth in Jordan: Findings from the Jordan Stillbirth and Neonatal Deaths Surveillance (JSANDS) system

Abstract: Background Annually, 2.6 million stillbirths occur around the world, with approximately 98% occurring in low- and middle-income countries. The stillbirth rates in these countries are 10 times higher than the rates in high-income countries. Methods An electronic stillbirths and neonatal deaths surveillance system (JSANDS) was established in five large hospitals located in three of the largest cities in Jordan in August 2019. JSANDS was developed as a secure on-line data entry system to collect, organize, anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“… 5 The perinatal outcome could be improved by early identification (ID) and management of women’s complications 6 since these happen mostly during the antepartum period. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The perinatal outcome could be improved by early identification (ID) and management of women’s complications 6 since these happen mostly during the antepartum period. 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 The perinatal outcome could be improved by early identification (ID) and management of women's complications 6 since these happen mostly during the antepartum period. 7 Early ANC check-up facilitates women's meeting of the WHO recommendations, 8 and is the major requirement of WHO's positive pregnancy experience. 8 9 Specific to lowincome countries, WHO recommended early ANC initiation and a minimum of four ANC visits for effective ANC services.…”
Section: Introductionmentioning
confidence: 99%
“…JSANDS was rated by the system users as useful because it provides estimates of the PNN mortality rate and the causes of deaths overall according to other social and clinical determinants. This finding is supported by the fact that the JSANDS data were used by authors in previous studies [13,14] to determine the rate, determinants, and causes of stillbirths and neonatal deaths in Jordan. The researchers in these studies reported that the majority of neonatal deaths could have been prevented and have recommended specialized care to be provided to low-birth-weight neonates and those with respiratory problems by experienced health care providers [13].…”
Section: Discussionmentioning
confidence: 62%
“…The researchers in these studies reported that the majority of neonatal deaths could have been prevented and have recommended specialized care to be provided to low–birth-weight neonates and those with respiratory problems by experienced health care providers [ 13 ]. Moreover, the researchers reported that the majority of stillbirths registered by JSANDS occurred during the antepartum period, and they recommended that care should be taken for the early identification of high-risk pregnancies and ensuring adequate antenatal obstetric interventions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors like older maternal age ( 13 ), experiencing delays in getting treatment ( 14 ), high-risk pregnancy ( 15 , 16 ), lack of antenatal care visits ( 17 ), multiple pregnancies ( 18 ), and having chronic medical conditions ( 19 ) are some of the identified factors that can affect the adverse pregnancy outcome. Thus, adverse pregnancy outcomes can be prevented and treated with immunization, nutritional supplementation, and routine screening for specific diseases ( 20 ).…”
Section: Introductionmentioning
confidence: 99%